Prinsip Amanah Dalam Fiqih Muamalah Dan Kontribusinya Terhadap Peradaban Bisnis Islam - Zainal Arifin (CV JK Riset Publishing Group, 2026)
The background of this research is based on the urgency of implementing the principle of amanah (trust) in the Islamic business system, which is increasingly relevant in the era of global economic modernization. This research aims to examine and analyze the concept of amanah in fiqh muamalah and its contribution to the formation of a just and ethical Islamic business civilization. The method employed is qualitative research with a library research approach through document analysis, normative text study, and synthesis of relevant scientific literature. The results show that the principle of amanah has three main dimensions: transactional honesty, contractual responsibility, and institutional integrity. The conclusion of this study affirms that amanah is not merely a moral value but an epistemological and institutional foundation for Islamic business civilization, capable of providing solutions to the trust crisis in contemporary economics. mic education and the renewal of Muslim intellectual and moral culture.